Contemporary treatment of erectile dysfunction a clinical guide - McVary, Kevin T. (Contemporary endocrinology., 2010)
Erectile dysfunction can affect all age groups. Numerous physical and emotional risk factors may contribute to the problem. These risk factors can range from chronic diseases and medications to psychological factors. In the U.S. alone, it has been estimated that 18 to 30 million men suffer from erectile dysfunction. This number has increased significantly as awareness of the disorder has heightened. Researchers and health care professionals now have a better understanding of what causes erectile dysfunction and the effective medications and non-medication treatments used to treat the condition. Comprehensive and state-of-the-art, Contemporary Treatment of Erectile Dysfunction: A Clinical Guide synthesizes the literature and covers all aspects of treating erectile dysfunction and other related male sexual dysfunctions. This invaluable title offers all physicians, residents, and fellows -- and even medical students and other health professionals such as nurse practitioners and physician assistants ? an essential reference for enhancing diagnosis and treatment of this debilitating disorder.